Langmuir probe measurement in a radio frequency inductively coupled argon plasma - Onga, C.L.; Chin, O.H.; Nisoab, Mudtorlep; Paosawatyanyangc, Boonchoat (2004)
A Langmuir probe diagnostic system is constructed to measure the plasma properties in a radio frequency (RF) inductively coupled Argon plasma. A passive compensation is incorporated into the Langmuir probe to provide the high impedance to the probe tip in the fundamental drive frequency of 13.56 MHz. This will enable the probe tip to follow the RF fluctuation in the plasma and allows the âdcâ probe characteristic to be measured. The properties of the RF inductively coupled Argon plasma are measured in the pressure range of 0.01 mbarâ0.4 mbar and the RF incident power from 20 Wâ280 W. The radial and axial distributions of the RF Argon plasma are also studied. Comparison of the results from the Langmuir probes with compensation and without compensation demonstrates the effect of the compensating component.